Melatonin in testes of infertile men: evidence for anti‐proliferative and anti‐oxidant effects on local macrophage and mast cell populations. (21st March 2014) - Rossi, S. P.; Windschuettl, S.; Matzkin, M. E.; Terradas, C.; Ponzio, R.; Puigdomenech, E.; Levalle, O.; Calandra, R. S.; Mayerhofer, A.; Frungieri, M. B.
Summary Melatonin acting through the hypothalamus and pituitary regulates testicular function. In addition, direct actions of melatonin at the testicular level have been recently suggested. We have described that melatonin inhibits androgen production in hamster Leydig cells via melatonin subtype 1a (mel1a) receptors and the local corticotrophin‐releasing hormone (CRH) system. The initial events of the melatonin/CRH signalling pathway have also been established. Melatonin and all components of the melatonergic/CRH system were also detected in Leydig cells of infertile men. This study attempted to search for additional targets of melatonin in the human testis, and to investigate the effects of melatonin on proliferation and the oxidative state in these novel target cells. To this aim, evaluation of human testicular biopsies of patients suffering from hypospermatogenesis or Sertoli cell only syndrome and cell culture studies were performed. Melatonergic receptors were found in macrophages (MACs) and mast cells (MCs) of the human testis. In biopsies of patients suffering idiopathic infertility, melatonin testicular concentrations were negatively correlated with MAC number per mm2 and TNFα, IL1β and COX2 expression, but positively correlated with the expression of the anti‐oxidant enzymes SOD1, peroxiredoxin 1 and catalase. Melatonin inhibited proliferation and the expression of pro‐inflammatory cytokines and cyclooxygenase 2 (COX2) in both the human non‐testicular THP‐1 MAC cell line and primary cell cultures of hamster testicular MACs. In the human HMC‐1 MC line, melatonin increased the expression of anti‐oxidant enzymes and decreased reactive oxygen species (ROS) generation. The results reveal new testicular targets of melatonin and describe anti‐proliferative and anti‐inflammatory effects of this hormone on testicular MACs. Furthermore, melatonin might provide protective effects against oxidative stress in testicular MCs.